2001
DOI: 10.1054/bjoc.2001.1858
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis of the CHK2gene in families with hereditary breast cancer

Abstract: Recently CHK2 was functionally linked to the p53 pathway, and mutations in these two genes seem to result in a similar Li–Fraumeni syndrome (LFS) or Li–Fraumeni-like syndrome (LFL) multi-cancer phenotype frequently including breast cancer. As CHK2 has been found to bind and regulate BRCA1, the product of one of the 2 known major susceptibility genes to hereditary breast cancer, it also more directly makes CHK2 a suitable candidate gene for hereditary predisposition to breast cancer. Here we have screened 79 Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
2

Year Published

2002
2002
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 19 publications
(14 reference statements)
4
54
2
Order By: Relevance
“…Two of the variants, a missense variant 470T4C (I157T) in exon 3 and a frameshift mutation 1100delC in exon 10, were the same as previously reported in patients with Li -Fraumeni syndrome (Bell et al, 1999), breast (Allinen et al, 2001;Vahteristo et al, 2002), and prostate cancer (Dong et al, 2003). The frameshift 1100delC mutation has been proven to result in the loss of kinase activity (Wu et al, 2001), and I157T variant has been shown to be defective in its ability to bind and phosphorylate Cdc25A, one of its normal substrates (Falck et al, 2001).…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…Two of the variants, a missense variant 470T4C (I157T) in exon 3 and a frameshift mutation 1100delC in exon 10, were the same as previously reported in patients with Li -Fraumeni syndrome (Bell et al, 1999), breast (Allinen et al, 2001;Vahteristo et al, 2002), and prostate cancer (Dong et al, 2003). The frameshift 1100delC mutation has been proven to result in the loss of kinase activity (Wu et al, 2001), and I157T variant has been shown to be defective in its ability to bind and phosphorylate Cdc25A, one of its normal substrates (Falck et al, 2001).…”
Section: Resultssupporting
confidence: 61%
“…It has a slightly higher frequency among patients with unselected prostate cancer than among control individuals and it is strongly associated with family history of the disease. However, according to the previous reports, the I157T allele does not make a significant contribution to breast cancer susceptibility (Allinen et al, 2001;Schutte et al, 2003). Therefore, the association with this allele is less conclusive.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…140 controls screened for variants found in case Offit et al (2002) ATM screened in 37 cases with Hodgkin's disease, 10 of whom also had breast cancer. 128 controls screened for variants found in cases Allinen et al (2002) 215 familial breast cancer cases, 85 nonfamilial breast cancer cases and 200 controls screened for eight ATM mutations Chenevix-Trench et al (2002) 525 or 262 breast cancer cases and 381 or 68 controls screened for T7271G and IVS10-6T>G, respectively Spurdle et al (2002) 1300 breast cancer cases and 600 controls screened for T2119C and C3161G Bernstein et al (2003) 1149 breast cancer cases screened for T7271G and IVS10-6T>G Thorstenson et al (2003) ATM screened in approximately 270 individuals with a family history of breast and/or ovarian cancer, 60% of whom had breast cancer and 52 controls. Additional controls screened for L1420F and/or IVS10-6T>G Sommer et al (2003) ATM screened in 47 breast cancer cases and 47 controls Angele et al (2003) ATM screened in 51 breast cancer cases.…”
Section: Molecular Evidence For Breast Cancer Risk In Atm Heterozygotesmentioning
confidence: 99%
“…In humans, CHEK2 inactivation is thought to mediate a moderately increased risk for breast and possibly prostate cancers (Allinen et al, 2001;Meijers-Heijboer et al, 2002;Seppala et al, 2003;Cybulski et al, 2004). Germline mutations were initially identified in families with Li Fraumeni-like multicancer syndromes lacking the characteristic mutation in p53 (Bell et al, 1999).…”
mentioning
confidence: 99%